O “Cenógrafo”-Heraldista do Estado Novo: O “Cenógrafo”-Heraldista do Estado Novo - Morais-Alexandre, Paulo (Eikón / Imago, 2025)
The important intervention of the Portuguese heraldist Franz-Paul de Almeida Langhans is stood up, registered, and analysed. He is the responsible for the most relevant creations in terms of Heraldry during the “Estado Novo” era, despite never having particularly interested in the areas of family, municipal or ecclesiastical heraldry. This production took place mainly in the third quarter of the 20th century in Portugal, within the scope of the visual structuring - the image, and even scenographic - the spectacle, of what was called the Corporate State. This heraldist had very significant activity in several areas of Heraldry, such as civil corporate heraldry, the heraldry of the Portuguese Armed Forces, the heraldry of overseas and national domains. A critique is also made of the work he produced, both in terms of heraldic science and in aesthetic terms, this already within the scope of Art History. Finally, his activity as an author is summarized, namely as a researcher and theorist in the Armaria area.